In Vitro Susceptibility Of Tigecycline Among Acinetobacter Baumanii Clinical Isolates From a Hospital in Indonesia - Veronica Wiwing; Cucunawangsih Cucunawangsih (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Acinetobacter baumanii (A. baumanii) has arisen as the most important cause of nosocomial infection, typically in severely ill patients with many comorbidities and medical supportive devices. Tigecycline is a therapeutic option for treating this infection because of its potential ability against wide spectrum of bacterias, including multi-drug resistance A. baumannii (MDRAB). Our study determine the in vitro susceptibility of tigecycline against A. baumanii isolates and the emergence of MDRAB. The frequency of isolates that were not inhibited at MIC ≤ 0.5 µg/ml was 50.46%, at MIC = 1µg/ml was 2.38%, and at MIC = 2 µg/ml was 19.07%. The susceptibility rate of tigecycline against A. baumanii was 68.27% in 2015, 79.58% in 2016, and 67.87% in 2017. In vitro result demonstrated that tigecycline had good value of MIC against A. baumanii at the range of 0.5 to 2 µg/ml.